Success of chemolithoautotrophic SUP05 and Sulfurimonas GD17 cells in pelagic Baltic Sea redox zones is facilitated by their lifestyles as K‐ and r‐strategists. (26th May 2017) - Rogge, Andreas; Vogts, Angela; Voss, Maren; Jürgens, Klaus; Jost, Günter; Labrenz, Matthias
Summary: Chemolithoautotrophic sulfur‐oxidizing and denitrifying Gamma ‐ (particularly the SUP05 cluster) and Epsilonproteobacteria (predominantly Sulfurimonas subgroup GD17) are assumed to compete for substrates (electron donors and acceptors) in marine pelagic redox gradients. To elucidate their ecological niche separation we performed 34 S 0, 15 NO 3 − and H 13 CO 3 − stable‐isotope incubations with water samples from Baltic Sea suboxic, chemocline and sulfidic zones followed by combined phylogenetic staining and high‐resolution secondary ion mass spectrometry of single cells. SUP05 cells were small‐sized (0.06–0.09 µm 3 ) and most abundant in low‐sulfidic to suboxic zones, whereas Sulfurimonas GD17 cells were significantly larger (0.26–0.61 µm 3 ) and most abundant at the chemocline and below. Together, SUP05 and GD17 cells accumulated up to 48% of the labelled substrates but calculation of cell volume‐specific rates revealed that GD17 cells incorporated labelled substrates significantly faster throughout the redox zone, thereby potentially outcompeting SUP05 especially at high substrate concentrations. Thus, in synopsis with earlier described features of SUP05/GD17 we conclude that their spatially overlapping association in stratified sulfidic zones is facilitated by their different lifestyles: whereas SUP05 cells are streamlined, non‐motile K ‐strategists adapted to low substrate concentrations, GD17 cells are motile r ‐strategists well adapted to fluctuating substrate and redox conditions.